Analysis of Novel Drug-Resistant Human Cytomegalovirus DNA Polymerase Mutations Reveals the Role of a DNA-Binding Loop in Phosphonoformic Acid Resistance - Park, Kye Ryeong; Kim, Young-Eui; Shamim, Amen; Gong, Shuang; Choi, Soo-Han; Kim, Kyeong Kyu; Kim, Yae-Jean; Ahn, Jin-Hyun (Frontiers in Microbiology, 2022)
The appearance of drug resistant mutations in UL54 DNA polymerase and UL97 kinase genes is problematic for the treatment of human cytomegalovirus (HCMV) diseases. During treatment of HCMV infection in a pediatric hematopoietic cell transplant recipient, H600L and T700A mutations and E576G mutation were independently found in the UL54 gene. Foscarnet (FOS; phosphonoformic acid) resistance by T700A mutation is reported. Here, we investigated the role of novel mutations in drug resistance by producing recombinant viruses and a model polymerase structure. The H600L mutant virus showed an increase in resistance to ganciclovir (GCV) by 11-fold and to FOS and cidofovir (CDV) by 5-fold, compared to the wild-type, while the E756G mutant virus showed an increase in resistance to FOS by 9-fold and modestly to CDV by 2-fold. With the FOS resistant T700A mutation, only H600L produced increased FOS resistance up to 37-fold, indicating an additive effect of these mutations on FOS resistance. To gain insight into drug resistance mechanisms, a model structure for UL54 polymerase was constructed using the yeast DNA polymerase as a template. In this model, HCMV DNA polymerase contains a long palm loop domain of which H600 and T700 are located on each end and T700 interacts with the FOS binding pocket. Our results demonstrate that H600L and E756G mutations in UL54 polymerase are novel drug resistant mutations, and that the acquisition of both H600L and T700A mutations in the DNA binding loop confers increased resistance to FOS treatment, providing novel insights for the mechanism acquiring foscarnet resistance.